Evaluation of Software Development Investments : A Real Options Approach - Sánchez, Marisa Analía (2011)
Software development projects are exposed to multiple sources of uncertainty. This uncertainty has an enormous impact in the investment economic value. The variability of a software development project payoff can be represented by the volatility of the project value over the analyzed period. The aim of this work is to define a framework to estimate the volatility of IT investments that takes into account all relevant information that has impact on project value, and show how to use this volatility estimation in a real options analysis. The suggested method could help IT managers produce a well-structured valuation process in software development investment decision-making, and understand the interactions between software process, market environment, financial issues and options value in a clear way.